The Quest for the Absolute
228 p.
Keywords: Hegel once said that philosophy is the "world stood on its head" and Karl Marx credited his own philosophic genius with setting the Hegel ian world right side up again. But both of these intellectual Atlases of the philosophical sphere that hid before our mind's eye a symbol bears further reflection. Philosophy down the ages has always involved at least two elements, first, the universe of being as its objective pole and second, man gazing into this crystallic sphere as the subjective pole. The "world" of Hegel and Marx and of most philosophers can be interpreted to mean the world we know and live in and about which all philosophers wonder. Thus for the philosopher - whoever he be - the concern of his interest is not limited to any particular segment of reality and no thing is off-limits to the beams of his mental radar. Yet this scope seems to many too vast and proud an enterprise. The philosopher seems to leap upon his horse and ride off in all directions at once. He is the day dreamer who indulges in fantasy and escapes from the world of practical concern and anxiety. On the other hand the reflective person must concede that it is the ideas ofthe philosophers more than the strategems of the generals that have shaped history and destinies.